UV-induced hydrogen-atom transfer and hydrogen-atom detachment in monomeric 7-azaindole isolated in Ar and n-H2 matrices. Issue 18 (20th April 2017) - Nowak, Maciej J.; Reva, Igor; Rostkowska, Hanna; Lapinski, Leszek
Abstract : Upon UV excitation, theN1H form of 7-azaindole isolated in an Ar matrix transforms intoN7H, C3H tautomers and the 7-azaindolyl radical; whereas onlyC3H and 7-azaindolyl radical products are photogenerated in solid H2 environment. Abstract : Photochemical transformations were investigated for monomers of 7-azaindole isolated in low-temperature Ar and normal-H2 (n-H2 ) matrices. The most stableN1H tautomer was the only form of the compound populated in Ar and n-H2 matrices before any irradiation. Upon exposure of Ar matrices to UV ( λ > 270 nm) light, two higher-energy tautomersN7H andC3H were photoproduced. Additionally, spectral signatures of the photogenerated 7-azaindolyl radical were also found. All of these photoproducts were experimentally observed for the first time. So far, theN7H tautomer had been known only as a transient species, appearing upon relaxation of photoexcited hydrogen-bonded dimers or complexes. For 7-azaindole isolated in an n-H2 matrix and irradiated at λ > 270 nm, only theC3H tautomer and the 7-azaindolyl radical were photogenerated, whereas theN7H tautomer was not photoproduced at all. The drastic dependence of photogeneration of theN7H form on the matrix environment (solid Ar or solid n-H2 ) is as a characteristic feature of a specific class of UV-induced hydrogen-atom-transfer processes occurring in matrix-isolated heterocycles.